Validasi Instrumen Pengembangan Video Pembelajaran Berbantuan Kinemaster Pada Materi Kelas VII Semester 2 SMP/MTs: Hasil Riset - M. Dino Parlaungan; Zulfah Zulfah; Astuti Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2022)
This research is motivated by the learning process that is carried out online and offline with reduced time to achieve learning objectives optimally and causes students' interest in learning to decrease. This study aims to produce quality instrument validation that will be used in assessing kinemaster-assisted mathematics learning videos. Development research was carried out using the Plomp model. The Plomp model consists of 3 stages, preliminary research, prototyping phase and assessment phase. The subjects of this research are 3 expert validators who are competent in their fields. This study uses instruments of validity, practicality and effectiveness. The research data were collected using observation sheets, interviews and questionnaires. Data analysis techniques used are preliminary data analysis, validity data analysis, practicality data analysis and effectiveness data analysis. Based on the results of the assessment of the interview sheets, observations and questionnaires using instrument validation, it is stated that the three assessment sheets are in the very valid category, so that the interview, observation and questionnaire sheets can be used to obtain assessment data and information on research needs.